Assessment of Rhinoplasty Outcomes with FACE-Q Rhinoplasty Module: Norwegian Linguistic Validation and Clinical Application in 243 Patients - Kalaaji, Amin (Plast Reconstr Surg Glob Open, 2019)
Patient satisfaction after rhinoplasty is a growing area of research. The FACE-Q Rhinoplasty Module, used to assess these values, requires translation to national languages. METHODS: Fourteen questions assessing the Satisfaction with Nose Scale and Adverse Effects Checklist of FACE-Q Rhinoplasty Module were translated to Norwegian with adherence to the Mapi Research Trust guidelines. Answers were processed by QuestBack anonymously. Of the 243 patients undergoing rhinoplasty at Oslo Plastic Surgery Clinic, 214 patients were reachable by e-mail. RESULTS: Response rates to the pre- and postoperative questionnaire were 23% and 32%, respectively. Responses for somewhat or very satisfied with the nose (pre- versus postoperative) were: overall size of the nose (16.3% versus 61.7%); how straight the nose looks (22.4% versus. 58.3%); how well the nose suits the face (12.2% versus 60%); length of the nose (20.4% versus 68.4%); width of the nose at the bottom (26.6% versus 55%); bridge of the nose (14.3% versus 55%); how the nose looks in photographs (10.2% versus 50%), and tip of the nose (16.3% versus 48.3%). Adverse effects (pre- versus postoperative) were moderate or extreme difficulty breathing through the nose (28.6% versus 35%); tenderness (6.1% versus 23.7%); skin of the nose looking thick or swollen (14.6% versus 30.5%); and unnatural bumps or hollows on the nose (55.1% versus 53.3%). CONCLUSIONS: Satisfaction levels in rhinoplasty patients are not as high as in other cosmetic surgery procedures, such as breast augmentation. However, compared with baseline, satisfaction levels showed great improvement postoperatively. The Rhinoplasty Module seems useful in evaluating outcome of rhinoplasty. We encourage application of this clinical outcome of rhinoplasty in and among centers.